ANTIBACTERIAL AND ANTIBIOFILM ACTIVITY OF QUERCUS INFECTORIA GALLS ON ROTHIA DENTOCARIOSA ISOLATED FROM DENTAL CARIES - AMBULKAR S; TALE V; KHILARI S; PAWAR J (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study aimed to study Quercus infectoria gall extract for phytochemical analysis, antibacterial, and antibiofilm activity against Rothia dentocariosa isolated from dental caries. Methods: R. dentocariosa was isolated, characterized, and identified by 16S rRNA sequence and also checked for biofilm formation ability. Phytochemical analysis of Q. infectoria aqueous gall extracts was carried out. Antibacterial and antibiofilm activity was performed using agar well diffusion method and microtiter plate assay, respectively. Results: Bacterial isolate from dental caries was identified as R. dentocariosa by 16s rRNA sequencing technique with accession number MH824681 obtained from NCBI. Phytochemical analysis of Q. infectoria aqueous gall extract revealed the presence of alkaloids, phenol, tannin, glycosides, phenolic compound, and flavonoids. Significant antibacterial activity was observed with 19.00 (±7.07) mm diameter zone of inhibition. The biofilm inhibition assay was performed by microtiter plate method indicated 92.89% inhibition of bacteria at the concentration of 100 mg/mL of aqueous extract. Conclusion: The results indicated the efficacy of Q. infectoria gall extracts that could be explored as an alternative to current treatment.